Extracellular production of avicelase by the thermophilic soil bacterium Bacillus sp. SMIA-2 - Luciana Ribeiro Coutinho Oliveira; João Batista Barbosa; Meire Lelis Leal Martins; Marco Antonio Martins (Acta Scientiarum. Biological Sciences, 2014)
Nowadays, the isolation of new bacterial strains that produce enzymes with novel properties is a subject of great relevance to the scientific community. This study, in order to search for producers of new cellulase strains, investigated the avicelase production by thermophilic Bacillus sp. strain SMIA-2. The best avicelase activity was observed in a culture medium containing 0.5% (w v-1) avicel and 0.5% (w v-1) corn steep liquor with initial pH 7.5-8.0 incubated at 50oC. When avicel was replaced in the medium by the treated sugarcane bagasse (0.5%, w v-1) the avicelase activity levels were not affected. Studies on the avicelase characterization revealed that the optimum pH of the enzyme was found to be 8.5 and the enzyme retained more than 80% of its activity after incubation at room temperature for 2h at pH 6.5-8.5. The optimum temperature of this enzyme was 70oC and the enzyme retained 67% of the original activity after 20 min. of heat treatment at 70oC. Avicelase was stimulated by Mn2+ and Co2+, whereas Hg2+ greatly inhibited the enzyme activity